Transthyretin Amyloid Fibril Disrupting Activities of Extracts and Fractions from Juglans mandshurica Maxim. var. cordiformis (Makino) Kitam. - Niraj Chaudhary; Ryoko Sasaki; Tsuyoshi Shuto; Masato Watanabe; Teppei Kawahara; Mary Ann Suico; Takeshi Yokoyama; Mineyuki Mizuguchi; Hirofumi Kai; Hari Prasad Devkota (Molecules, 2019)
Transthyretin-related amyloidosis is a slowly progressive disorder caused by deposition of insoluble amyloid plaques formed by fibrillization of mutant or defective transthyretin (TTR) monomers that leads to neurodegeneration and organ failure. Thus, any compound exhibiting TTR amyloid formation inhibitory activity or TTR amyloid fibril disrupting activity might be a potential candidate for the development of therapies for these disorders. Our aim in this study was the evaluation of the TTR amyloid fibril disrupting potential of extracts of leaves and immature fruits of two Juglans plants, i.e., Juglans mandshurica var. sachalinensis and Juglans mandshurica var. cordiformis. The TTR amyloid fibril disrupting activity was measured by Thioflavin-T (ThT) assay and PROTEOSTAT® Protein aggregation assay methods. A fifty percent acetone extract of the fruits of Juglans mandshurica var. cordiformis showed strong amyloid fibril disrupting activity, and was further fractionated using different solvents. Ethyl acetate and n-butanol fractions showed significant activity in both assays. Syringic acid was isolated and identified as main compound in both of these fractions; however, it did not show any activity. Furthermore, some of the previously reported compounds from Juglans plants including naphthoquinone derivatives and phenolic compounds were evaluated to identify the potential bioactive compounds. Among them, juglone, a naphthoquinone derivative showed promising activity. However, juglone also showed strong cytotoxicity in HEK293 cells. Thus, future studies should focus on the isolation and identification of naphthoquinone derivatives or other compounds from Juglans plan ts with potent bioactivity and low cytotoxicity.